PENDAMPINGAN KETRAMPILAN PEMBUATAN TAS TALI KUR DARI BAHAN GELAS BEKAS BAGI KOMUNITAS BUNDA BISA DESA CUMPLENG BRONDONG LAMONGAN - Latifah, Eny; Muawanah, Rifatul; Arifatin, Nanik; Martiwi, Wanala Abdillaika; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Assistance in order to provide training for the management of used materials from used mineral water cups to be managed into products that are aesthetic and have high selling value. The community service method used is Participatory Action Research (PAR) with the stages of observation, action and evaluation. The result of the assistance was that the mothers and teenagers who joined the Bunda Bisa community of Yatim Mandiri Cumpleng Brondong Lamongan were able to create a product in the form of a 1-colour or 2-colour Kur String Bag by utilizing used glasses of mineral water. The benefits are that mothers and adolescents can increase their creativity, increase income, as well as establish brotherhood and increase the entrepreneurial spirit.